English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

this is what they say for the problem:

For f(x) = 8x - 9, find f(-3).

2006-12-07 04:36:34 · 7 answers · asked by jenningscingular 1 in Science & Mathematics Mathematics

7 answers

f(-3)=8(-3)-9
-24-9
=-33

2006-12-07 04:38:05 · answer #1 · answered by raj 7 · 0 0

f(-3) = 8(-3) - 9 = -24 -9 = -33

2006-12-07 12:38:13 · answer #2 · answered by Manoj C S 2 · 0 0

f(-3) = 8(-3) - 9 = -24 -9 = -33

2006-12-07 12:38:07 · answer #3 · answered by Michael 4 · 0 0

f(-3)=8(-3)-9
=-24-9
=-33

2006-12-07 12:38:42 · answer #4 · answered by Dupinder jeet kaur k 2 · 0 0

Cheater.

2006-12-07 13:08:53 · answer #5 · answered by trigam41 4 · 0 0

f(x) = 8x - 9

x = - 3

f(-3) = 8(- 3) - 9

f(-3) = - 24 - 9

f(- 3) = - 33

- - - - - s-

2006-12-07 12:43:42 · answer #6 · answered by SAMUEL D 7 · 0 0

f(-3)=8(-3) -9

f(-3)=-24-9

f(-3)=-33

f(-3)/-3= -33/-3

f=11 so

11(-3)= -33

2006-12-07 12:53:25 · answer #7 · answered by kristina55 2 · 0 0

fedest.com, questions and answers